Nutritional supplementation practices during pregnancy in Village Development Committees of Morang District, Nepal - Sah, RB; Subedi, L; Shah, U; Jha, N; Pokharel, PK (Journal of College of Medical Sciences-Nepal, 2015)
BACKGROUND Pregnancy is a critical period for both woman and baby from a nutritional perspective. Poor nutrition, during pregnancy is associated with adverse maternal and fetal outcomes. However, due to various factors, pregnant women do not increase the quality or quantity of diet during pregnancy. OBJECTIVE To find out the prevalence of nutritional supplementations taken during pregnancy and to find out the association between sociodemographic characteristics and nutritional supplementations taken during pregnancy. MATERIALS AND METHODS The cross-sectional study was conducted from 1st March to 14th March, 2014 among the residents of Rangeli VDC of Morang District in Eastern Nepal where 300 households were taken as subjects. Semistructured questionnaire was used and face to face interview was conducted. Chi-square test was applied to find out the association between sociodemographic characteristics and nutritional supplementations taken during pregnancy. RESULT The problem of not taking extra nutritional supplementations during pregnancy is common and has become a key public health concern. Lack of education of wife and husband led some of the respondents not taking more nutritional supplementations during pregnancy. CONCLUSION The problem of not taking extra nutritional supplementations during pregnancy is common and has become a key public health concern. Lack of education of wife and husband led some of the respondents not taking more nutritional supplementations during pregnancy. DOI: http://dx.doi.org/10.3126/jcmsn.v10i2.12948 Journal of College of Medical Sciences-Nepal, 2014, Vol.10(2); 10-17